NOTES ON CALISCELIDAE FROM TURKEY, WITH FIRST RECORD OF THE TRIBE ADENISSINI DLABOLA (HEMIPTERA, FULGOROMORPHA) - Gnezdilov, Vladimir M.; Ozgen, Inanc (Amer Entomol Soc, 2024)
Caliscelidae records from Turkey are summarized. The tribe Adenissini Dlabola is recorded for the first time from the country after Perissana bispinata (Dlabola, 1980) collected in Mardin Province. New records for Ommatidiotus iranicus Horv & aacute;th, 1905 and Bruchoscelis peculiaris (Horv & aacute;th, 1904) are given.
Keywords: Adenissina; Bruchoscelis; new record; Ommatidiotus; Perissana; planthopper